Differences Between Lemon Aromatherapy and Hypnobirthing in Reducing Nausea and Vomiting of Pregnant Women in the First Trimester - Sari, Lutfiana Puspita; Nurrasyidah, Rahmi (Poltekkes Kemenkes Surakarta, 2023)
Backgrounds: Nausea and vomiting are discomforts of pregnancy about which 50–90% of pregnant women complain in the first trimester. Hypnobirthing and lemon aromatherapy are complementary therapies that can relax so that endorphins are produced and will reduce nausea. Methods: The study design is a pre-experimental research method. Research conducted in June–August 2022 at Puskesmas Klaten Selatan. A total of 50 pregnant women who suffered nausea and vomiting were recruited using accidental sampling. The data collection technique uses a PUQE-24 score. Data analysis used univariate and bivariate methods. Univariate performed the distribution frequency calculation. Bivariate data analysis using the Wilcoxon test because the data is not normally distributed. Differences in nausea and vomiting between the two groups using the Mann-Whitney test. Results: Lemon aromatherapy effectively reduces nausea and vomiting (p-value < 0.05). Hypnobirthing can effectively reduce nausea and vomiting (p-value < 0.05). We found a significant difference between the score of nausea and vomiting for lemon aromatherapy and hypnobirthing (p-value < 0.05). Both post-tests were in the range of mild nausea and vomiting, but the post-test score of lemon aromatherapy was lower than hypnobirthing, where the average post-test score of lemon aromatherapy was 1.43, while the post-test mean score of hypnobirthing was 6.43. Conclusion: Lemon aromatherapy and hypnobirthing relaxation can effectively reduce nausea and vomiting. There is a significant difference between nausea and vomiting scores in pregnant women who are given lemon aromatherapy and hypnobirthing.